Terahertz Microstrip Patch Antennas For The Surveillance Applications - Mahmud, Rashad Hassan (Kurdistan Journal of Applied Research, 2020)
This paper presents a new design of the microstrip patch antenna operated at the terahertz frequencies (700-850 GHz). The conventional microstrip patch antenna dimensions shrink to a few microns when operating at such terahertz frequencies. Thus, the design of the patch and its feeding network will be miniaturized extremely, and their fabrications would be extremely difficult. In this paper, the configuration of the proposed microstrip patch antenna is suited in a way that it can be modeled using multilayers structure. This multilayer structure facilitates the modeling, and considering its fabrication. The proposed microstrip antenna has been designed using three layers. The top layer is used to model the rectangular patch; while the second layer is for the substrate, and the bottom layer is for the ground plane. The physical dimensions of the layers and the fed-line are optimised using the microwave Computer Simulation Technology (CST) simulator in order to enhance the electrical parameters of the antenna such as antenna realised gain, bandwidth, total and radiation efficiencies, and radiation patterns. In addition to that, the impact of the physical dimensions of the rectangular patch on controlling the resonant frequency of the dominant mode (TM01) have been investigated. Keeping the lower and higher propagating modes out of the frequency band of interest is another aspect which has been addressed in this paper. The antenna has been simulated, and its realised gain fluctuates from 6.4 dBi to 9.7 dBi over the operating frequency range (700-850 GHz). Also, it provides extremely large reflection coefficient bandwidth (S11) which it is below -10 dB over the entire operating frequency band. The total efficiency is more than 75 %. Due to its simplicity and providing large bandwidth, the proposed antenna could be of interest in many security and surveillance applications.